Selected indicators of mental health in the elderly - the participants the University of the Third Age - Martina Tomagová; Ivan Farský; Ivana Bóriková; Mária Zanovitová (University of Ostrava, 2016)
Aim: The aim of the research study is to identify the selected indicators of mental health, such as meaning of life, experience of well-being, hope, and feelings of loneliness and depression in the elderly participating in the University of the Third Age, in relation to their age and gender. Design: A quantitative descriptive study. Methods: The selection of respondents was deliberate. The sample consisted of 147 seniors with a mean age of 67.4 (± 4.9) years enrolled at the University of the Third Age at Jessenius Faculty of Medicine, Comenius University. Data were collected by means of self-assessment scales - the Life Meaningfulness Scale, Snyder´s Hope Scale, the Emotional Habitual Subjective Well-being Scale, the Loneliness Scale, and the Geriatric Depression Scale. Results: Seniors considered their life meaningful, and expressed a high level of hope. Their emotions were predominately positive. We identified low levels of loneliness and found no indication of depressed mood. We identified significant differences between men and women in evaluation indicators of mental health only in the frequency of positive emotions. Conclusion: The study indicates the presence of salutogenic factors affecting the mental health of the sample of seniors in the process of active aging. The results could form the basis for implementing preventive strategies in clinical nursing practice.